Cross-sectional comparative study of socio-demographic and health profile of children in a NGO- run open house and street children in a metropolitan city - Malgaonkar, Aniruddha A.; Kartikeyan, S. (International Journal of Research in Medical Sciences, 2016)
Background: Street children are underprivileged urban children who suffer poverty, deprivation of education, vulnerability to various types of abuse, lack of supervision by adults, and with varying status of street-based existence and contact with their families. The study compares the socio-demographic and health profiles of children in a NGO-run Open House and street children. Methods: Respondents satisfying intake criteria were interviewed using a pre-tested questionnaire and their height and weight were measured and the data were statistically analysed. Results: 72% were aged between 12-16 years. Their occupations included rag picking, unorganised labour, street vending, cleaning vehicles, hotel work and begging. The reasons for street living were parental abuse, poverty, parental death, or peer pressure. Between the two groups of children, there were significant differences in frequencies of genital lesions (p=0.014; OR=0.465), injuries (p=0.01; OR=0.5), scabies (p=0.01; OR=0.31), and pyoderma (p=0.03; OR =0.38). A majority from both groups chewed tobacco regularly, some were addicted to more than one substance and had started using addictive substances due to peer pressure or to alleviate depression. Conclusions: Multi-pronged interventions ought to focus on improving income levels and housing of impoverished families, curbing parental abuse, and providing educational and health care facilities, establishing more number of drop-in Open Houses, providing avenues for legal income, and educating on the hazards of promiscuity and substance abuse.